2019
DOI: 10.1186/s12711-019-0492-4
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study explores the genetic determinism of host resistance to Salmonella pullorum infection in chickens

Abstract: Background Salmonella infection is a serious concern in poultry farming because of its impact on both economic loss and human health. Chicks aged 20 days or less are extremely vulnerable to Salmonella pullorum (SP), which causes high mortality. Furthermore, an outbreak of SP infection can result in a considerable number of carriers that become potential transmitters, thus, threatening fellow chickens and offspring. In this study, we conducted a genome-wide association study (GWAS) to detect pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The susceptibility or resistance to Salmonella is related to the host genetics ( 27 , 28 ). Several studies have discovered candidate genes associated with the death and carrier state of chickens after Salmonella infection ( 29 , 30 ). Our previous study revealed 43 host genetic markers associated with S .…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility or resistance to Salmonella is related to the host genetics ( 27 , 28 ). Several studies have discovered candidate genes associated with the death and carrier state of chickens after Salmonella infection ( 29 , 30 ). Our previous study revealed 43 host genetic markers associated with S .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, FBXW7 has also been shown to have multiple functions in virus infection via interacting with diverse host molecules such as SHP2 ( Song et al., 2017 ), mTOR ( Xu et al., 2016 ), and NS5B ( Chen et al., 2016 ) in immune responses. Although a previous study reported that FBXW7 was downregulated after Salmonella infection ( Li et al., 2019 ), the function of FBXW7 in the immune responses during bacterial infection is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent research into the Ehrlichia chaffeensis TRP120 HECT E3 Ub ligase showed that it could target FBXW7 as a substrate to promote E. chaffeensis infection via maintaining the stability of Notch, c-Jun, and c -Myc and supporting cell survival ( Wang J. Y. et al., 2020 ). Recently, a genome-wide association study identified that FBXW7 was significantly downregulated in the chicken after infection with Salmonella pullorum , suggesting it may also play a role in controlling S. pullorum infection ( Li et al., 2019 ). Moreover, two studies of FBXW7’s function in macrophages suggested that FBXW7 played crucial roles in macrophage-pathogen interaction ( Song et al., 2017 ; Wang J. Y. et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This gene has been associated with the dominant white coat color locus (W) which produces lethal disorders in the very early stages of gestation (W/W-genotype) [ 58 ], thus affecting fertility by indirect pathways. Similarly, recently, Velie, et al [ 78 ] identified a negative effect of inbreeding on ECA1 quantitative trait loci (QTL) in a large population of Norwegian-Swedish Coldblooded trotters. However, the same region was previously reported by Gottschalk et al [ 50 ] in association with the number of motile sperm, suggesting that the reduction in fertility from inbreeding could be partially mediated by a reduction in sperm quality ( Table 4 ).…”
Section: Inbreeding Molecular Homozygosity and Reproduction In Homentioning
confidence: 93%